Nicodemus - Goulder, Michael Douglas (Scottish journal of theology, 1991)
Nicodemus is the hero of many a Trinity Sunday sermon.2 The leader of the Jews, the master of Israel, comes humbly to Jesus, by night to the Light of the World. He does not believe much (like the preacher perhaps), but he has the heart of the matter, ‘We know that thou art a teacher come from God’. Jesus teaches him the profound truth of man's need for rebirth, and he is converted. He stands up for his faith pluckily against the hostility of his peers — ‘Does our Lawjudge a man…?’; and in the end it is he who buries Jesus, with a royal anointment of a hundred litres of myrrh.